Hunting introduced species in Indonesia New Guinea - FREDDY PATTISELANNO; MAX J. TOKEDE; AGUSTINA Y. S. AROBAYA; GUN MARDIATMOKO; AUGUST E. PATTISELANNO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Pattiselanno F, Tokede MJ, Arobaya AYS, Mardiatmoko G, Pattiselanno AE. 2023. Hunting introduced species in Indonesia New Guinea. Biodiversitas 24: 3045-3050. Hunting in tropical forests is mostly performed to obtain animal protein sources, generate income, and enact cultural activities. However, it is acknowledged that hunting was conducted indiscriminately, killing both native and introduced species. This study aimed to describe hunting activities along the lowland coastal forests in Tambrauw Districts. Fieldwork was carried out between June 2011 and December 2012 in eleven villages across the Abun and Amberbaken sub districts of Tambrauw Districts, Papua Barat Province of Indonesia. Information about hunting was gathered through interviews with 220 hunters (focus respondents; 20 hunters in each village). Therefore, to gain an overall picture of hunting in the sampled villages, we distributed 100 questionnaires, not including those focal respondents, and 800 were returned from 11 villages. This study revealed hunting for trading (49%) compared to consumption (44%) and the rest (7%) hunting for others (festive, pest, and trophy). The hunting is classified as very frequent (2-3 days per week) by 10%, frequent (weekly and fortnightly) by 41%, and rarely (monthly) by 49% of hunters. Active techniques used were bows and arrows, spears and blades were primarily used by 38%, and hunting with dogs was 29% by inhabitants in the studied villages. On the other hand, passive hunting using snares and guns were used by 28% and 5% of hunters, respectively. Hunters reported nine main prey species had been hunted, and the prey consisted of six mammal and three bird species. Two of the nine species were introduced species, i.e., rusa deer and wild pig; they provided the largest amount of meat and fat and were economically profitable. Other native species were also hunted, although not much as introduced ones. The average catch per hunting trip was 2 individuals (2.42 ± SD 1.93). In this study, hunting introduced species is important because it is more profitable while protecting the native species or those of conservation concern.